2004
DOI: 10.1007/s00247-004-1285-6
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow parameters of the superior mesenteric artery as an early predictor of intestinal dysmotility in preterm infants

Abstract: Pathological blood flow parameters in the SMA can predict problems of intestinal motility and tolerance of enteral feeding. With the early detection of these problems a prompt start of adequate therapy to avoid complications is possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 25 publications
1
46
0
7
Order By: Relevance
“…19,20 It is not clear if the attenuated SMA BFV was owing to CPAP-related decreases in cardiac output, nor if bowel-related concerns with CPAP relate to our finding of attenuated increases in postnatal SMA BFV in infants on CPAP. However, other investigators have reported that attenuated increases in postnatal SMA BFV are associated with intestinal dysmotility, 2 and with feeding intolerance. 3,4 Ongoing studies in our NICU are designed to further elucidate the relationship between CPAP, postnatal SMA BFV and clinical outcomes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…19,20 It is not clear if the attenuated SMA BFV was owing to CPAP-related decreases in cardiac output, nor if bowel-related concerns with CPAP relate to our finding of attenuated increases in postnatal SMA BFV in infants on CPAP. However, other investigators have reported that attenuated increases in postnatal SMA BFV are associated with intestinal dysmotility, 2 and with feeding intolerance. 3,4 Ongoing studies in our NICU are designed to further elucidate the relationship between CPAP, postnatal SMA BFV and clinical outcomes.…”
Section: Discussionmentioning
confidence: 93%
“…1 There is increasing evidence that the rate of increase in SMA BFV may have clinical significance. Greater increases in postnatal SMA BFV during the first week of life in preterm infants are reportedly associated with less intestinal dysmotility, 2 and with better tolerance to enteral feedings. 3,4 Intestinal blood flow is regulated by numerous factors including cardiovascular status, neural control, humoral substances and local control.…”
Section: Introductionmentioning
confidence: 97%
“…4 We previously reported that CPAP administration was associated with an attenuation of the postnatal increase in superior mesenteric artery blood flow velocity (SMA BFV) in preterm infants. 5 Attenuated increases in postnatal SMA BFV are reportedly associated with intestinal dysmotility 6 and with feeding intolerance. 7 Our objective was to further investigate the effect of CPAP on intestinal blood flow velocity by measuring pre-and postprandial SMA BFV in preterm infants when they were receiving CPAP ('on CPAP') and after CPAP was discontinued ('off CPAP').…”
Section: Introductionmentioning
confidence: 99%
“…Blood flow velocity in the superior mesenteric artery, measured using Doppler ultrasound in 478 very-low-birth-weight neonates (<1500 g), was predictive of subsequent intestinal dysmotility and correlated with the quantity of tolerated enteral feeding. 12 In this case, the pulsatility index showed 95% sensitivity and 82% specificity in predicting intestinal dysmotility. Color Doppler U/S may be useful in determining bowel viability, which can be characterized by bowel wall thickness and perfusion.…”
Section: Ultrasonographymentioning
confidence: 67%